Penggunaan Informasi Keuangan untuk Memprediksi Keuntungan Investasi bagi Investor di Pasar Modal - Parawiyati Parawiyati; ambar woro hastuti; edi subiyantoro (The Indonesian Journal of Accounting Research, 2013)
The objective of this research is to test relationship of the ability financial information in predicting the benefit of equity investment that consist of earnings and cash flow. Financial information includes; changes’ earnings, account receivable, inventory, selling and administration expenses, and gross profit to sales ratio. The reason for using financial variables is based on the evidence that previous researchers used the same variables as significant indicators of the effects of changes in earnings and cash flows.This research has gotten a sample of 288 financial reports, which were published among 1998-1994 by manufacturing firms, which quoted on the Jakarta Stock Exchange. The first hypothesis is that financial information will predict the changes in earnings and cash flow for one year or more. While the second, they are provide incremental prediction ability in the presence of cash flow.The statistical results show that financial information is useful in predicting changes in earnings and cash flow. Earnings and gross profit to sales ratio were significant in predicting changes in earnings one year ahead, but not significant for predicting cash flow. The significant variables in predicting the changes in earnings and cash flow ahead were selling and administrative expenses and gross profit to sales ratio. The tests whether earnings provide incremental predictive in the presence of cash flow, the result of statistics shows that it was not significant, however cash flow is a better predictor of cash flow.